Estratégias de marketing digital e comunicação não verbal no discurso político eleitoral: uma abordagem do caso da campanha eleitoral de Helder Barbalho em 2022 pelo Instagram - Velani, Paula Barbosa (Universidade Federal de São Carlos, 2024)
Political communication on social media plays a crucial role in strengthening the connection between politicians and their audience. The growing use of these new media in the 21st century is revolutionizing communication, facilitating more dynamic interactions among users. The use of digital marketing resources and non-verbal communication not only enables the creation of assertive content but also contributes to building a charismatic leader figure on social media. In this ever-evolving digital era, this research aimed to address a case of effective political engagement during election campaigns, with Instagram, emphasizing its focus on images and videos, standing out as a key platform for political communication. To that end, the research was based on literature about digital marketing and content marketing techniques. Furthermore, it investigated relevant non-verbal elements to build a credible, positive, and persuasive political image. Methodologically, with a qualitative approach, the research conducted a single case study of Helder Zahluth Barbalho's 2022 gubernatorial campaign for the State of Pará, focusing on video and image content on the Instagram platform. Thus, this work aims to contribute to the debate on new forms of relationship through digital media and provide insights for those who wish to enter the political arena effectively.
Digital marketing strategies and nonverbal communication in political electoral discourse: an analysis of Helder Barbalho's 2022 electoral campaign on Instagram
Keywords: Engajamento; Política; Redes sociais; Relacionamento; Engagement; Politics; Social media; Relationship; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO::ESTUDOS ELEITORAIS E PARTIDOS POLITICOS